Knowledge and practice of nursing personnnel regarding the care of neonates under phototherapy at Paropakar Shree Panch Indra Rajyalaxmi Devi Prasuti Griha, Thapathali, Kathmandu - Shrestha, Santoshi (Journal of Kathmandu Medical College, 2014)
Background: High neonatal mortality is a reflection of very poor neonatal care. Hence a specialist should be able to take up leadership role in neonatal care to prevent high mortality and morbidity rate. The study was carried out to determine the knowledge and practice of the nursing personnel regarding the care of neonates with phototherapy. Objectives: To assess the knowledge and skills/practice of nurses regarding the care of neonates with phototherapy. Methods: Descriptive and exploratory research design was adopted for the study from 15th to 30th April, 2007 for two weeks at Paropakar Shree Panch Indra Rajyalaxmi Devi Prasuti Griha, Thapathali, Kathmandu. A semistructured questionnaire was designed to collect the data from 50 respondents working in different wards and they were selected by using Purposive sampling technique. The data collected were analysed and interpreted based on descriptive and inferential statistics. The level of knowledge score was converted into percentage and overall adequacy of knowledge was graded according to the following criteria:- If score > 75% highly knowledgeable If score 50 % to 75% moderate knowledge If score <50% inadequate knowledge1. Results: The findings revealed that the majority of the respondents 28 (56%) were highly knowledgeable (the knowledge level of the respondents more than 75 %) and 22 (44%) respondents were with average knowledge (more than 50% and less than75%). No respondents were below 50% level (below 50%). Conclusion: The study attempts to determine the knowledge and practice of nursing staffs regarding the care of neonates with phototherapy. According to the data and information of the respondents the nursing personnel should be provided with in-service education training in relation to care of neonates with phototherapy. This study will be helpful for providing information about existing knowledge and practices of nursing personnel regarding phototherapy. It will help to provide knowledge about the strength and weakness of the services provided by the hospital regarding phototherapy for future researcher. DOI: http://dx.doi.org/10.3126/jkmc.v2i2.10631 Journal of Kathmandu Medical College, Vol. 2, No. 2, Issue 4, Apr.-Jun., 2013, page: 84-88